2010
DOI: 10.2337/db10-0699
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I and Genetic Susceptibility to Type 1 Diabetes

Abstract: OBJECTIVEWe report here genotyping data and type 1 diabetes association analyses for HLA class I loci (A, B, and C) on 1,753 multiplex pedigrees from the Type 1 Diabetes Genetics Consortium (T1DGC), a large international collaborative study.RESEARCH DESIGN AND METHODSComplete eight-locus HLA genotyping data were generated. Expected patient class I (HLA-A, -B, and -C) allele frequencies were calculated, based on linkage disequilibrium (LD) patterns with observed HLA class II DRB1-DQA1-DQB1 haplotype frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
197
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(209 citation statements)
references
References 18 publications
9
197
1
2
Order By: Relevance
“…Previous studies have shown several independent signals within the MHC region in multiple autoimmune diseases, including RA and systemic lupus erythematosus (54)(55)(56)(57), and specifically with HLA-A in type 1 diabetes (54). The data are less clear for MHC class III because of the strong LD there ( Figure 4C).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 66%
“…Previous studies have shown several independent signals within the MHC region in multiple autoimmune diseases, including RA and systemic lupus erythematosus (54)(55)(56)(57), and specifically with HLA-A in type 1 diabetes (54). The data are less clear for MHC class III because of the strong LD there ( Figure 4C).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 66%
“…This historical bias was due to the long-known association between diabetes and HLA class II predisposing and protective alleles. The recent recognition that HLA class I alleles can also modulate T1D risk (61,64,65) has further emphasized the role of CD8CT cells. More recently, a direct association between these T cells and b-cell destruction has been suggested in humans.…”
Section: T-cell Responses To Insulinmentioning
confidence: 99%
“…More than 20 putative diabetes predisposing genes have been identified, but most of them have only a weak association, and in many cases the association has been difficult to confirm. The one exception is the HLA genes, which are thought to contribute as much as 50% of the genetic risk for Type 1 (DM) (Noble, Valdes et al 2010). Although HLA genes may be necessary, by themselves they seem not to be sufficient to produce the disease.…”
Section: Triggers Of Autoimmune Cascadementioning
confidence: 99%